Association between insulin therapy and risk of liver cancer among diabetics: a meta-analysis of epidemiological studies. Issue 1 (January 2018) - Liu, Xiao-Li; Wu, Hua; Zhao, Long-Gang; Xu, Hong-Li; Zhang, Wei; Xiang, Yong-Bing
Abstract : As the results of the association between insulin therapy and risk of liver cancer among diabetics have been inconsistent in epidemiological studies, we conducted a meta-analysis to quantify this issue. Data of relevant epidemiological studies were collected by searching articles in PubMed, Web of Science, and Embase till 29 June 2017. Random-effects models were employed to combine study-specific risks. Five cohort studies and nine case–control studies were included in our meta-analysis with 285 008 patients with diabetes mellitus and 4329 liver cancer cases. When we compared insulin-use group with noninsulin use group in patients with diabetes mellitus, we observed a statistically significant association between insulin therapy and liver cancer, with an overall relative risk of 1.90 (95% confidence interval: 1.44–2.50, I 2 =76.1%). We did not find heterogeneity between subgroups stratified by study characteristics and adjusted confounders, except for subgroups related to 'follow-up years' of cohort studies. The combined estimate was robust across sensitivity analysis, and no publication bias was detected. Our results indicated that insulin therapy was associated with elevated incidence of liver cancer among diabetics. Given the high prevalence of diabetes, avoiding excess or unnecessary insulin use to control the blood glucose may offer a potential public health benefit in reducing liver cancer risk. Further studies are warranted to investigate the types, doses, and treatment duration of insulin use in large sample size or cohort of diabetic patients. Abstract : Supplemental Digital Content is available in the text.